Term -1 NCERT CBSE Class 9 Prove the following:(is)a^3-b^3=(a-b)(a^2+ab+b^2)​

Question

Term -1 NCERT CBSE Class 9 Prove the following:(is)a^3-b^3=(a-b)(a^2+ab+b^2)​

in progress 0
Remi 2 weeks 2021-11-15T10:58:33+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-15T11:00:08+00:00

    Step-by-step explanation:

    to prove this just take any 2 values for a and b

    eg. say a=1 b= 0

    LHS = 1³-0³= 1

    RHS= (1-0)(1²+1×0+0²)=1×1= 1

    LHS= RHS

    HENCE PROVED

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )